2014
DOI: 10.1016/j.jprot.2013.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Aspergillus nidulans secretome during colonisation of cork cell walls

Abstract: Cork, the outer bark of Quercus suber, shows a unique compositional structure, a set of remarkable properties, including high recalcitrance. Cork colonisation by Ascomycota remains largely overlooked. Herein, Aspergillus nidulans secretome on cork was analysed (2DE).Proteomic data were further complemented by microscopic (SEM) and spectroscopic (ATR-FTIR) evaluation of the colonised substrate and by targeted analysis of lignin degradation compounds (UPLC-HRMS). Data showed that the fungus formed an intricate n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 69 publications
(99 reference statements)
1
20
0
Order By: Relevance
“…Mycelial and extracellular proteins were obtained and quantified as previously described (Carvalho et al, 2013;Martins et al, 2014a). Mycelial (100 mg powder mixed with 20 mg poly(vinyl)polypyrrolidone) and extracellular (concentrated using 10 kDa centrifugal devices) proteins were precipitated with cold acetone containing 10% w/v trichloroacetic acid and 60 mM dithiothreitol (DTT).…”
Section: Protein Samples Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Mycelial and extracellular proteins were obtained and quantified as previously described (Carvalho et al, 2013;Martins et al, 2014a). Mycelial (100 mg powder mixed with 20 mg poly(vinyl)polypyrrolidone) and extracellular (concentrated using 10 kDa centrifugal devices) proteins were precipitated with cold acetone containing 10% w/v trichloroacetic acid and 60 mM dithiothreitol (DTT).…”
Section: Protein Samples Preparationmentioning
confidence: 99%
“…Protein isoelectric focusing, electrophoresis, staining, image acquisition and analysis followed previously described methods (Carvalho et al, 2013;Martins et al, 2014a). The gels were stained with flamingo dye (Bio-Rad) or colloidal coomassie blue for image acquisition or spot excision, respectively.…”
Section: Two-dimensional Gel Electrophoresis (2de)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on A. nidulans colonisation of cork revealed that suberin remained unaltered [103] probably because the outermost lignin-enriched cell wall layers hampered its degradation. Here we have shown that A. nidulans was able to utilise suberin macromolecules as sole carbon source (Figure 1b) and that the fungus also underwent sexual development (Figure 4) and boosted secondary metabolism (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although the degradation of suberin has not been extensively examined, it has been attributed to soil fungal populations (14). When Aspergillus nidulans was grown on suberized cell walls, the degradation of the suberin aromatic domain was corroborated by the identification of some degradation products, whereas the aliphatic domain remained virtually intact (20). However, a whole-genome transcriptome analysis of A. nidulans , which was conducted in order to identify the main pathways involved in suberin degradation, proposed that initial suberin degradation involved ester hydrolysis, possibly through the actions of cutinase 1 and some lipases (21).…”
mentioning
confidence: 99%